Aplikasi Pengaduan Masyarakat terhadap Pelayanan Dikantor Camat Wanokaka Berbasis Web (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to design and develop a web-based public complaints application aimed at improving the quality of public services at the Wanokaka Sub-district Office. This application was developed to facilitate the public in submitting various types of service-related complaints, while also providing a mechanism for monitoring the resolution status in a more transparent and accountable manner. The development method used was the System Development Life Cycle (SDLC), which includes the stages of needs analysis, system design, implementation, and functional testing. The resulting system includes key features such as a complaint form, status notifications, complaint history, and a dedicated dashboard for officers to manage and follow up on reports. The results indicate that this application not only accelerates the complaint handling process but also improves the effectiveness of communication between the public and the sub-district. With this application, the complaints process becomes more structured and responsive, and is expected to increase public trust in the quality of public services in Wanokaka Sub-district.